Characterization of forced degradation products of pazopanib hydrochloride by UHPLC‐Q‐TOF/MS and in silico toxicity prediction. (4th June 2015) - Patel, Prinesh N.; Kalariya, Pradipbhai D.; Sharma, Mahesh; Garg, Prabha; Talluri, M. V. N Kumar; Gananadhamu, S.; Srinivas, R.
Abstract : Pazopanib (PZ), an anti‐cancer drug, was subjected to forced degradation under hydrolytic (acid, base and neutral), oxidative, photolytic and thermal stress conditions as per International Conference on Harmonization guidelines. A selective stability indicating validated method was developed using a Waters Acquity UPLC HSS T3 (100 × 2.1 mm, 1.7 µm) column in gradient mode with ammonium acetate buffer (10 m m, pH 5.0) and acetonitrile. PZ was found to degrade only in photolytic conditions to produce six transformation products (TPs). All the TPs were identified and characterized by liquid chromatography/atmospheric pressure chemical ionization–quadrupole‐time of flight mass spectrometry experiments in combination with accurate mass measurements. Plausible mechanisms have been proposed for the formation of TPs. In silico toxicity was predicted using TOPKAT and DEREK softwares for all the TPs. The TP, N4‐(2, 3‐dimethyl‐2H‐indazol‐6‐yl)‐N4‐methylpyrimidine‐2, 4‐diamine, was found to be genotoxic, whereas all other TPs with sulfonamide moiety were hepatotoxic. The data reported here are expected to be of significance as this study foresees the formation of one potential genotoxic and five hepatotoxic degradation/transformation products. Copyright © 2015 John Wiley & Sons, Ltd.